IMPOLITENESS UTTERANCES IN “22 JUMP STREET” MOVIE : PRAGMATICS APPROACH - Dian Fitriani; Zia Hisni Mubarak (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This research aimed to identify the impoliteness strategies that is employed in 22 Jump Street. The researcher used the theory of impoliteness strategies developed by Culpeper. In this research, the researchers used descriptive qualitative analysis to examine impoliteness methods in this study. The movie "22 Jump Street" is the subject of the study. Data for this study were collected using an observational methodology and a non-participatory strategy. The data was analyzed using pragmatic identification methods once it had been processed. As a result of the research, the movie contained 15 utterances. Those utterances contained the use impoliteness strategies, including 5 bald on record impoliteness, 4 positive impoliteness, 2 negative impoliteness, 3 mock politeness or sarcasm, and 1 withhold politeness.